2017
DOI: 10.1002/aenm.201700032
|View full text |Cite|
|
Sign up to set email alerts
|

New Acetylene‐Bridged 9,10‐Conjugated Anthracene Sensitizers: Application in Outdoor and Indoor Dye‐Sensitized Solar Cells

Abstract: In this report, a pivotal improvement in the performance of dye‐sensitized solar cells has been achieved, thus taking it one step closer toward the commercialization. Through the stepwise modification on the anthracene‐based organic sensitizers, the alteration of alkyl to alkoxy chain and incorporation of electron deficient moieties in the new sensitizing dyes TY3, TY4, and TY6 are found to play a significant role in the efficiency enhancement. The dye TY6, when tested under 1 sun (AM 1.5G) illumination, is fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
78
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(84 citation statements)
references
References 80 publications
5
78
1
Order By: Relevance
“…MM-6 showed the highest performance among all, that is, 24.37 % under 600 lux, 27.58 %u nder 1000 lux, and 27.82 %u nder www.chemsuschem.org 2500 lux. These PCEs are comparable to those of the N719based cells under similarc onditions, that is, 17.21 %( 600 lux), 20.10 %( 1000 lux), and 24.63 %( 2500 lux), respectively.T he performance of MM-6 is only slightly lower than the recordhigh dye (28.56 %a t6 000 lux) reported by Tingare et al [60] Using DCA as co-absorbenti mproved the performance of MM-6 to 25.42 %( 600 lux), 27.40 %( 1000 lux), and 28.95 % (2500 lux). Moreover,t he co-sensitization of MM-3 and MM-6 resultedi nr emarkable PCEs of 27.76 %( 600 lux), 28.84 % (1000 lux), and 30.45 %( 2500 lux).…”
Section: Dssc Performanceunder Indoor Lightmentioning
confidence: 63%
See 1 more Smart Citation
“…MM-6 showed the highest performance among all, that is, 24.37 % under 600 lux, 27.58 %u nder 1000 lux, and 27.82 %u nder www.chemsuschem.org 2500 lux. These PCEs are comparable to those of the N719based cells under similarc onditions, that is, 17.21 %( 600 lux), 20.10 %( 1000 lux), and 24.63 %( 2500 lux), respectively.T he performance of MM-6 is only slightly lower than the recordhigh dye (28.56 %a t6 000 lux) reported by Tingare et al [60] Using DCA as co-absorbenti mproved the performance of MM-6 to 25.42 %( 600 lux), 27.40 %( 1000 lux), and 28.95 % (2500 lux). Moreover,t he co-sensitization of MM-3 and MM-6 resultedi nr emarkable PCEs of 27.76 %( 600 lux), 28.84 % (1000 lux), and 30.45 %( 2500 lux).…”
Section: Dssc Performanceunder Indoor Lightmentioning
confidence: 63%
“…[59] Tingare et al reported that an acetylene-based anthracene sensitizer yieldeda PCE of 28.56 %u nder 6000 lux T5 fluorescent light. [60] Recently, Desta et al used ap yrazine-incorporated panchromatic sensitizer that reached PCE values of 18.85 %a nd 27.17 %, respectively,u nder 300 and 6000 lux of T5 fluorescent light. [61] By mixing our dyes MM-3 and MM-6,w ea chieved PCE valueso f 27.76 %, 28.74 %, and 30.45 %u nder 600, 1000, and 2500 lux, respectively,u nder TL84 fluorescent light.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the MS3 sensitizer, TY3 (D-π-A) and TY6 (D-A-π-A) were also synthesized. TY6 has the best PCE (up to 8.80%) [36]. To study the relationship between structure and properties, we used the theory of density functional theory (DFT) and time-dependent density functional theory (TD-DFT) to calculate the three-molecular-geometry, electron injection, dye regeneration, and optical properties, and results confirmed that its excellent performance was due to its excellent J SC and V OC characteristics.…”
Section: Introductionmentioning
confidence: 70%
“…The three molecules (MS3, TY3, and TY6) used in this article and the experimental data mentioned were obtain from [36,37], and other data were calculated using software such as the Gaussian 09 package. In addition, other data generated or analyzed during this study are available from the first and corresponding authors on reasonable request.…”
Section: Data Availabilitymentioning
confidence: 99%
“…The easy synthesis of the fused acene cores reduced the number of steps required for synthesizingt hese small-molecule donors. [18][19][20] Previously reporteda cene-basedsmall molecules have shownh igh hole mobilities, which was attributed to high crystallinity,but limited PCEs owing to inferiormiscibility between acene-based small molecules and fullerene derivatives. [21][22][23] Therefore, carrying out modifications of the molecular structures and optimizationso fm orphologies are of great importance for achievinge fficient exciton dissociation at the donor/acceptor interface and high PCEs in OPVs by using acene-based small-molecule donors.…”
Section: Introductionmentioning
confidence: 99%